1984
DOI: 10.1002/art.1780270611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of static and cyclic compressive loading on articular cartilage plugs in vitro

Abstract: The influence of static and intermittent stress on articular cartilage metabolism was examined in vitro. Full‐thickness plugs of cartilage from femoral condyles of normal adult dogs were cultured while static or cyclic stresses were applied for 2 hours. The plugs were then incubated under atmospheric pressure for 2 hours in medium containing radioactive label, to provide measurements of net synthesis of glycosaminoglycan (GAG) or protein. As a control, cartilage from the same knee was cultured in the apparatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
2
5

Year Published

1986
1986
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(122 citation statements)
references
References 20 publications
5
110
2
5
Order By: Relevance
“…The frequency of mechanical stimulation can also affect matrix synthesis but this was not examined in this study. We used a stimulation frequency of 1 Hz because other investigations have shown that frequencies between 0.01 and 1 Hz stimulate matrix synthesis [2,7,22,[26][27][28]33,37], whereas frequencies less than 0.01 Hz suppress matrix synthesis [26][27][28]331.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of mechanical stimulation can also affect matrix synthesis but this was not examined in this study. We used a stimulation frequency of 1 Hz because other investigations have shown that frequencies between 0.01 and 1 Hz stimulate matrix synthesis [2,7,22,[26][27][28]33,37], whereas frequencies less than 0.01 Hz suppress matrix synthesis [26][27][28]331.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical environment of the tissue regulates, in part, cartilage development and maintenance in viva [17], leading to investigations on the effect of compressive forces on extracellular matrix synthesis in cartilage explants [2,22,33,37,43] and scaffolds seeded with chondrocytes [7,. However, native articular cartilage not only transmits compressive joint loads to the underlying subchondral bone, but also provides a lowfriction interface between the contacting cartilage surfaces of the joint [29].…”
mentioning
confidence: 99%
“…29, No. 1 (January 1986) either increased or decreased net GAG biosynthesis, depending on the duration of loading (18).…”
Section: Composition and Glycosaminoglycan Metabolism Of Articular Camentioning
confidence: 99%
“…Previous studies have shown that small dynamic oscillations imposed upon strain levels of 10-200/1 at frequencies of 0.002-0.1 Hz stimulate S-GAG synthesis by as much as 50% in cartilage explants [22,33]. In addition, intermittent compression at high duty cycles ( 2 4 s of applied load followed by 2-1 1 s of release) also stimulates sulfated proteoglycan synthesis [24,29]. These results suggest a causal relationship between mechanical loading and matrix metabolism in articular cartilage.…”
Section: Introductionmentioning
confidence: 99%